Klimaat, biodiversiteit en de christelijke traditie - Boersema, Jan J. (Theologia reformata, 2024)
In this article, I will show how the two major environmental issues of our time, man-made climate change and biodiversity decline, are connected to Christian thought about creation and history. Views on the character of time and related notions of progress and growth are relevant to the first issue; views on changes in creation as a result of the fall to the second. Finally, I will argue that the pursuit of sustainability requires a supporting narrative. Christianity, despite its fraught past, has important ingredients for such a narrative.